Pengenalan Dan Design Logo Kemasan Untuk Umkm Dalam Era Digital : Strategi Meningkatkan Pemasaran Di Desa Sungai Siput - Abel Tri Rahma; Aisyah Az Zahra; Hisma Rahman; Jaya Rizaldi Fajri; Melis Anita; M.iqbal; Salsabila Putri; Siti Khofifah Amara; Sri Wahyuni (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The purpose of this University of Riau KKN activity is to provide assistance to UMKM in terms of utilizing digital technology to market products and improve product branding, especially for UMKM in Sungai Siput Village. There are 3 UMKM in Sungai Siput Village, namely UMKM that sell oyster mushrooms, handicrafts and herbal medicine, which are experiencing a decline in sales so they need to implement new strategies, one of which is product branding and digital marketing. Assistance is provided to utilize technology to increase sales, create logo designs for social media and also to be used on packaging, so that people can get to know the product itself better. The result of this activity is the formation of a new logo and a new name for product branding from UMKM. Apart from that, UMKM owners also receive education regarding the theory of digital product marketing through effective and targeted social media.